Surgical Menopause and Nonvertebral Fracture Risk among Older U.S. Women - Vesco, Kimberly K. (2012)
OBJECTIVE: To determine whether older postmenopausal women with a history of bilateral oophorectomy prior to natural menopause (surgical menopause) have a higher risk of nonvertebral, postmenopausal fracture than women with natural menopause. METHODS: We used 21 years of prospectively collected incident fracture data from the ongoing Study of Osteoporotic Fractures (SOF), a cohort study of community dwelling women without previous bilateral hip fracture who were age 65 or older at enrollment, to determine the risk of hip, wrist, and any nonvertebral fracture. Chi square and t-tests were used to compare the two groups on important characteristics. Multivariable Cox proportional hazards regression models stratified by baseline oral estrogen use status were used to estimate the risk of fracture. RESULTS: Baseline characteristics differed significantly between the 6,616 women within SOF who underwent either surgical (1,157) or natural (5,459) menopause, including mean age at menopause (44.3 ±7.4 versus 48.9 ±4.9 years, p<.001) and current use of oral estrogen (30.2% vs 6.5%, p<.001). Fracture rates were not significantly increased for surgical versus natural menopause, even among women who had never used oral estrogen (hip fracture, hazard ratio [HR] 0.87, 95% confidence interval [CI] 0.63–1.21; wrist fracture HR 1.10, 95% CI 0.78–1.57; any nonvertebral fracture HR 1.11, 95% CI 0.93–1.32). CONCLUSION: These data provide some reassurance that the long-term risk of nonvertebral fracture is not substantially increased for postmenopausal women who experienced premenopausal bilateral oophorectomy, compared to postmenopausal women with intact ovaries, even in the absence of postmenopausal estrogen therapy.